2012
DOI: 10.1097/nen.0b013e31824ea078
|View full text |Cite
|
Sign up to set email alerts
|

Moderate Traumatic Brain Injury Triggers Rapid Necrotic Death of Immature Neurons in the Hippocampus

Abstract: Traumatic brain injury (TBI) causes cell death predominantly in the cerebral cortex but there is additional secondary cell death in the hippocampus. We previously found that the majority of the dying cells in the mouse hippocampus are newborn immature granular neurons in a mouse model of lateral controlled cortical impact (CCI) injury with a moderate level of impact. It is not known how long this selective cell death in the hippocampal dentate gyrus lasts, and how it is induced. Using Fluoro-Jade B and immunoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
76
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(82 citation statements)
references
References 88 publications
(79 reference statements)
5
76
0
1
Order By: Relevance
“…21,22 FJB staining is specific for damaged neurons and has been used as a reliable method to quantify post-CCI damage in the L-side of the brain. 23 Indeed, we detected extensive FJB signal in the L-side and no detectable signal in the C-side hippocampus of vehicle-treated CCI-exposed mice in low magnification images (Fig.…”
mentioning
confidence: 99%
“…21,22 FJB staining is specific for damaged neurons and has been used as a reliable method to quantify post-CCI damage in the L-side of the brain. 23 Indeed, we detected extensive FJB signal in the L-side and no detectable signal in the C-side hippocampus of vehicle-treated CCI-exposed mice in low magnification images (Fig.…”
mentioning
confidence: 99%
“…19 About 50% of immature neurons in the hippocampus die within 24 h after TBI with a moderate CCI injury. 19,21 Recent studies further show that TBI promotes NSPC proliferation in the adult, 20,[51][52][53][54][55][56][57][58][59] leading to increased generation of immature neurons. Thus, it is assumed that more immature neurons will be generated trying to compensate for TBI-induced immature neuron death.…”
Section: Discussionmentioning
confidence: 99%
“…19,21 The number of immature neurons in the epicenter reduced about 50% at 24 h after moderate TBI. 19 Our recent study found that pretreatment of DHF increased the number of immature neurons in the hippocampus following moderate TBI.…”
Section: Dhf Treatment Increased the Number Of Adult-born Immature Nementioning
confidence: 99%
See 2 more Smart Citations